A multi-subject accuracy study on granular jamming for non-invasive attachment of fiducial markers to patients - Wellborn, Patrick S.; Russell, Paul T.; Webster III, Robert J. (International journal for computer assisted radiology and surgery, 2020)
Purpose This short communication describes experimental evaluation of a new granular jamming cap (GJC) recently introduced in Wellborn et al. (Int J Comput Assist Radiol Surg 12(6):1069–1077, 2017 ). The contributions beyond [ 8 ] are (1) to evaluate accuracy across multiple human subjects, and (2) to determine how much of the accuracy improvement is attributable to improved fiducial marker arrangement alone, and how much is due to granular jamming. The motivation for this GJC is to improve the accuracy of image-guidance interfaces in transnasal skull base surgery. Accuracy depends on a rigid connection between tracked fiducial markers and the patient. By molding itself to the unique contours of the individual patient’s head and then solidifying, the GJC can firmly attach fiducial markers to a patient, increasing accuracy in the presence of disturbances. Methods A multi-subject study ( n = 8 ) was performed to evaluate the accuracy of the GJC compared to a clinically used headband-based fixation device, in the presence of simulated accidental bumping (light force and impact events) that could occur in a real-world operating room. Results The GJC reduced the average target registration error at the pituitary gland by 66% in our force experiments and 78% in our impact experiments, which were statistically significant reductions ( p < 0.001 ). Maximum target registration error was similarly reduced by 55% and 78% in the same two perturbation tests. Conclusion The GJC increases the accuracy of transnasal image-guidance under force and impact perturbations by more firmly, yet non-invasively, attaching fiducial markers to the patient. We find that granular jamming provides accuracy improvement beyond that associated with improved fiducial marker arrangement.